نماذج من مشاركات الرحالة العلماء المغاربية في المجتمع المكي في القرن 11 هـ. = 17 م. - نواب، عواطف بنت محمد بن يوسف (جامعة القصيم, 2018)
سكن بمكة المشرفة العديد من الجنسيات الإسلامية في القرن ‎11ه/ 17م؛ إما مجاورين مجاورة طويلة أو قصيرة، وربما قضى بها بعضهم بقية حياته إلى وفاته. وقد ساهمت هذه الجنسيات في حضارة وثقافة مكة المشرفة. ومن هؤلاء الذين عاشوا في مكة المشرفة المغاربة، الذين كانوا رسل العلم والثقافة والتاريخ، فكان منهم من نذر حياته لخدمة المجتمع المكي، ومنهم من تصدر لنشر العلم والتأليف، ومنهم من كانت له سلطة سياسية خدم بها المجتمع المكي، فالوضع في مكة المشرفة كان ملائماً سياسياً في تلك الفترة لاستقرار الجاليات الإسلامية، بالإضافة إلى ما كان يلقاه العلماء المغاربة من احترام متبادل بينهم وبين أشرف مكة المشرفة، فنتج عن ذلك رواج علمي وخاصة في علم الحديث الشريف، حق عد هذا القرن قرن علماء الحديث.
Many Islamic nationalities lived in Makah during the century of 11AH /17G for either long or short period and perhaps some of them spent the rest of his life there. These nationalities have contributed to the civilization and culture of Mecca supervisor. Among those who have lived in Mecca Moroccans, who were the apostles of science, culture and history, among whom was the devoted his life to serve Makah society, and some were issued for Science and authoring, and some were his political authority served by the Makah society, the situation in Mecca was politically convenient and helped the stability of the Islamic communities, in addition to what he receives Moroccan scientists of mutual respect between them and the supervision of Mecca "Al-Ashraf" and resulted in a scientific vogue, especially in the science of hadith, and made that century the Century of Hadith Scholars.
Keywords: التاريخ الإسلامي -- مكة المكرمة -- العلماء المغاربة -- التراجم